Longitudinal viral kinetic study of BK virus in renal transplant patients - A single-center study in Sri Lanka - K.D.S.T. Abeywardana; R.G.L.S. Rajamanthri; A.W.M. Wazil; N. Nanayakkara; M.A.R.V. Muthugala (Journal of Clinical Virology Plus, 2022)
Background: There is a strong association between high-level BK viraemia and the development of BK virus-associated nephropathy. Therefore, understanding the kinetics of BK virus replication following transplantation would be helpful in predicting high-level viraemia and the development of BKVAN. Objectives: This study was aimed to assess the incidence of BKV infection and the BK viral kinetics among renal transplant recipients in their first year following the transplant. Methods: This study was a retrospective descriptive study involving renal transplant recipients treated at National Hospital, Kandy, Sri Lanka. The patients were recruited from January 2018 to December 2019 and their demographic details and quantitative BKV PCR assay results were analysed during the first year following transplantation. Results: 297 patients were transplanted during the study period wherein, males predominated with 78.1% and 43.67 years old being the mean age (IQR: 35.50–53.0). The cumulative incidence of BK viraemia was 24.9% (n = 74). The mean age of the cohort with BK viraemia was 44.4 years (IQR: 36–54). Twenty percent (n = 13) of the female population had BKV viraemia, while 26.29% (n = 61) of the male population. Among patients with BK viraemia 12 had significant viraemia of 104IU/ml giving a cumulative incidence of significant viraemia was 4.04% and 10 of them (83.33%) had low levels of viraemia before showing significant viraemia. Conclusion: The presence of low-level viraemia in 83% of patients with significant viraemia proves the value of early routine screening to predict the development of significant BK viraemia and to take preventive measures.